PEMBUATAN BETWEEN CENTRE TEST BAR MESIN BUBUT UNIVERSAL - Febriani, Risky Ayu; Saksono, Novi; Candra, Addonis; Harja, Herma Budi; Fahlevi, Rivaldy Muhammad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The inspection tool commonly used during the manufacture and acceptance testing of new machine tools or repair of old machine tools is the test bar. The test bar is a mandrel for calibration aids representing an axis to be checked within a given value, either for run-out or for location (position and orientation) in relation to other machine components. Conditions and performance on the precision of the machine will affect the products produced from the production process. Thus, the use of a test bar for the precision of a machine tool is carried out through a calibration process. At present, the need for test bars for the machine tool calibration process in Indonesia is a product imported from outside (imported), even though the manufacture of test bars allows it to be done independently. In this study, the between centre test bar was redesigned and made based on ISO 230-11 standards with the subject of examination for the straightness of the sledding movement in the horizontal and vertical planes referring to and DIN 8605. The stages of making the between-centre test bar include turning, heat treatment, cylinder grinding, and measurement. The accuracy of the geometry, such as the alignment of the diameter between-centre test bar is carried out using a CMM (Coordinate Measuring Machine) machine. Furthermore, the between-centre test bar is tested on a universal lathe to determine its feasibility through the process of checking the alignment of the spindle axis with the machine table in the vertical and horizontal directions (calibration).